(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
In modern service-oriented economies, competitiveness is increasingly shaped not only by strategic or institutional factors but also by consumer behavior and perception. This paper examines service quality as a behavioral driver of competitiveness in the service sector. Unlike traditional approaches that treat service quality as one of many competitive factors, this study conceptualizes service quality as a mechanism influencing consumer behavior, loyalty, and market positioning. Based on a conceptual and analytical approach, the paper explores the relationship between perceived service quality and competitive outcomes in service markets. A conceptual framework is proposed to explain how service quality operates through consumer perception to shape competitiveness. The findings contribute to service economics and provide practical implications for service enterprises seeking sustainable competitive advantages.